1993
DOI: 10.1055/s-0038-1649591
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Production of Thromboxane B2 by Platelets of Diabetic Patients Is Normal at Physiological Concentrations of lonized Calcium

Abstract: SummaryPlatelets of patients with diabetes and no evidence of macroangiopathy produce normal amounts of thromboxane (Tx) B2 in vivo, whereas they usually show increased production in vitro. Since in vitro studies have been usually performed in citrated PRP, we tested the hypothesis that the discrepancy between in vivo and in vitro studies is due to the low concentration of plasma ionized calcium ([Ca 2+ ]o) that is present in citrated PRP. In fact, low [Ca 2+ ]o arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…Rather, we think that their results are in accord with well-established knowledge of the factors involved in ADPinduced TxA 2 generation: (1) ADP does not stimulate TxA 2 production directly; (2) it is the close platelet-to-platelet contact that is brought about by ADP-induced platelet aggregation that triggers the production of TxA 2 ; and (3) this effect is greatly enhanced and can be seen in most healthy individuals when [Ca ϩϩ ]o is decreased to micromolar levels. [2][3][4][5] Based on this interpretation, it is not surprising that the experiments performed by Jin et al showed that antagonists of P2Y 1 , P2Y 12 , or the fibrinogen receptor, which inhibit ADP-induced platelet aggregation, abolished the TxA 2 production. The dependency of TxA 2 production and the ensuing platelet secretion on platelet aggregation is demonstrated by the observation that no TxA 2 production or platelet secretion occurs from normal human platelets that are stimulated by ADP, even at high concentration, under conditions in which platelet aggregation does not occur: for instance, if the receptor function for adhesive proteins on ␣ IIb ␤ 3 is inhibited with inhibitory monoclonal antibodies or Arg-Gly-Asp-containing peptides, or, more simply, if the platelet suspension is not stirred.…”
Section: Adenosine Diphosphate (Adp) Does Not Induce Thromboxane a 2 mentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, we think that their results are in accord with well-established knowledge of the factors involved in ADPinduced TxA 2 generation: (1) ADP does not stimulate TxA 2 production directly; (2) it is the close platelet-to-platelet contact that is brought about by ADP-induced platelet aggregation that triggers the production of TxA 2 ; and (3) this effect is greatly enhanced and can be seen in most healthy individuals when [Ca ϩϩ ]o is decreased to micromolar levels. [2][3][4][5] Based on this interpretation, it is not surprising that the experiments performed by Jin et al showed that antagonists of P2Y 1 , P2Y 12 , or the fibrinogen receptor, which inhibit ADP-induced platelet aggregation, abolished the TxA 2 production. The dependency of TxA 2 production and the ensuing platelet secretion on platelet aggregation is demonstrated by the observation that no TxA 2 production or platelet secretion occurs from normal human platelets that are stimulated by ADP, even at high concentration, under conditions in which platelet aggregation does not occur: for instance, if the receptor function for adhesive proteins on ␣ IIb ␤ 3 is inhibited with inhibitory monoclonal antibodies or Arg-Gly-Asp-containing peptides, or, more simply, if the platelet suspension is not stirred.…”
Section: Adenosine Diphosphate (Adp) Does Not Induce Thromboxane a 2 mentioning
confidence: 99%
“…[2][3][4][5] (The widespread use of citrate as an anticoagulant in the preparation of platelet-rich plasma introduces the same artifact as suspending media without added CaCl 2 .) Despite this, Jin et al suggest that ADP-induced TxA 2 production may have physiological relevance in vivo, because [Ca ϩϩ ]o might be "drastically lower" 1(p196) at sites of thrombus formation.…”
Section: Adenosine Diphosphate (Adp) Does Not Induce Thromboxane a 2 mentioning
confidence: 99%
See 1 more Smart Citation
“…The platelet P2Y 12 receptor (P2Y 12 R) for adenosine 5 0 diphosphate (ADP) plays a central role in platelet function, hemostasis, and thrombosis. Patients with inherited P2Y 12 R defects display mild-to-moderate bleeding diatheses. Defects of P2Y 12 R should be suspected when ADP, even at high concentrations (≥ 10 lM), is unable to induce full, irreversible platelet aggregation.…”
mentioning
confidence: 99%
“…Defects of P2Y 12 R should be suspected when ADP, even at high concentrations (≥ 10 lM), is unable to induce full, irreversible platelet aggregation. P2Y 12 R also plays a role in inflammation: its role in the pathogenesis of allergic asthma has been well characterized. In addition, inhibition or genetic deficiency of P2Y 12 R has antitumor effects.…”
mentioning
confidence: 99%